Criminalization and International Human Rights. (2018) - Miller, Alice M.
Abstract : Human rights advocacy today engages with criminal law at international and national levels with a new and rather conflicted posture. It is reorienting from an approach that primarily treated human rights as a shield from (unjust) prosecutorial and carceral power, and toward one calling for criminal penalties and vigorous prosecutions as a remedy for harms. The human rights abuses for which state prosecution is invoked today include not only past and present state violations, such as torture, but crimes by non-state actors, such as sexual and gender-based violence. At the same time, paradoxically, many rights groups are calling for the review and reduction of criminal regulation of a range of sexual and reproductive health practices, including abortion, consensual sexual conduct outside of marriage (same sex, heterosexual, and sex for money), and HIV transmission.